2004
DOI: 10.1002/tea.20003
|View full text |Cite
|
Sign up to set email alerts
|

The role of discourse in group knowledge construction: A case study of engineering students

Abstract: This qualitative study examined the role of discourse (verbal elements of language) and Discourse (nonverbal elements related to the use of language, such as ways of thinking, valuing, and using tools and technologies) in the process of group knowledge construction of mechanical engineering students. Data included interviews, participant observations, and transcripts from lab sessions of a group of students working on their senior design project. These data were analyzed using discourse analysis focusing on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 19 publications
2
61
0
6
Order By: Relevance
“…Studies have shown keeping students not only engaged in engineering course content, but also in their educational community, can help strengthen a student's perception of where they fit and can contribute in the engineering world, which results in higher retention rates [13] [20] [31].…”
Section: ) Importance Of Cblmentioning
confidence: 99%
“…Studies have shown keeping students not only engaged in engineering course content, but also in their educational community, can help strengthen a student's perception of where they fit and can contribute in the engineering world, which results in higher retention rates [13] [20] [31].…”
Section: ) Importance Of Cblmentioning
confidence: 99%
“…Indeed, in contrast to our own view of disciplinary discourse as representing a particular way of knowing, Moje, Collazo, Carrillo & Marx (2001) in the following quote appear to suggest that Discourse is a particular way of knowing: "Any stretch of language (discourse) is always embedded in a particular way of knowing (Discourse)…" (p. 470). For a good illustration of the Discourse approach the reader is referred to Kittleson & Southerland (2004) who use the concept to analyze engineering students' group knowledge construction. Thus Gee's Discourse can be characterized, in relation to social identity, as including such things as students' epistemology, group dynamics, gender, social status, etc.…”
Section: Why Not Use "Big D" Discourse?mentioning
confidence: 99%
“…The purpose of shared scientific language is that it makes it possible for the students to communicate easily with each other and to reduce the problem quickly and routinely. The Engineering Physics group's behaviour shares many similarities with Kittleson and Southerland's (2004) case study on engineering discourse; rather than discussing concepts of science the engineering students only exchanged numbers or graphs with each other. Kittleson and Southerland explain this with that the students viewed themselves as being homogeneous with respect to academic ability, which had implications for how they communicated with each other, the students believed that they shared an understanding for engineering, and therefore could let data speak for itself, like the Engineering Physics students in our case study let the physics equations dominate the communication.…”
Section: Discussionmentioning
confidence: 99%